Implementasi Pembelajaran Mahārah al-Qirā’ah dengan Pendekatan Komunikatif di Lembaga Kursus Bahasa: Implementation of Reading Skills Learning with a Communicative Approach at a Language Course Institution - Al Haqiqy, Muhammad Syihabul Ihsan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The purpose of this study was to describe the implementation of reading skills instruction using a communicative approach, covering preparation, learning activities, and evaluation. This research uses a qualitative approach with a case study type. The subjects of this study involved teachers and students during reading skills lessons in the course class at Madrasatul Alsun Sidoarjo in the 2024 academic year. Data collection techniques included classroom observations during reading skills lessons, interviews with teachers and students, and documentation related to teaching materials, lesson plans, and teachers' evaluation results. Data analysis used the Miles and Huberman model, which includes data condensation, data display, and conclusion drawing. The findings of this study were as follows: First, the teacher created lesson plans, prepared two methods (question and answer and direct instruction), and arranged for two relevant media types, including concrete media and non-concrete media in the form of images, as well as established the learning objectives to be achieved. Second, the learning activities began with motivation by offering learning encouragement in a technical step where the teacher greeted the students, inquired about their well being, and checked their readiness to learn. For the core activities, communicative reading skills instruction was applied in several stages: introduction, expansion, and reinforcement. Third, in the evaluation activity, the teacher prepared a series of questions relevant to the reading texts that had been studied.